2019
DOI: 10.1093/toxsci/kfz045
|View full text |Cite
|
Sign up to set email alerts
|

BLT-Immune Humanized Mice as a Model for Nivolumab-Induced Immune-Mediated Adverse Events: Comparison of the NOG and NOG-EXL Strains

Abstract: Checkpoint inhibitors represent a new class of therapeutics in the treatment of cancer that has demonstrated remarkable clinical effectiveness. However, some patients have experienced serious immune-mediated adverse effects including pneumonitis, hepatitis, colitis, nephritis, dermatitis, encephalitis, and adrenal or pituitary insufficiency. These adverse events were not predicted by nonclinical studies. To determine if bone marrow-liver-thymus (BLT) immune humanized mice could demonstrate these adverse effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…22 NOG-BLT mice and NOG-EXL (expressing human GM-SCF and IL3) BLT mice were also used to demonstrate the induction of adverse reactions to anti-PD-1 therapy (nivolumab), including pneumonitis and hepatitis. 23 However, the BLT model presents several challenges for high-throughput screening, which include limited availability of human fetal tissues, ethical concerns with the procurement, the requirement for survival surgery and the lengthy time period required for immune system development (8 to 12 weeks). 48 The 2006 clinical trial using healthy volunteers with TGN1412 resulted in severe systemic inflammation that became life threatening in all recipients and correlated with a rapid cytokine release syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 NOG-BLT mice and NOG-EXL (expressing human GM-SCF and IL3) BLT mice were also used to demonstrate the induction of adverse reactions to anti-PD-1 therapy (nivolumab), including pneumonitis and hepatitis. 23 However, the BLT model presents several challenges for high-throughput screening, which include limited availability of human fetal tissues, ethical concerns with the procurement, the requirement for survival surgery and the lengthy time period required for immune system development (8 to 12 weeks). 48 The 2006 clinical trial using healthy volunteers with TGN1412 resulted in severe systemic inflammation that became life threatening in all recipients and correlated with a rapid cytokine release syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…21 Previous studies have suggested the potential of using immunodeficient mice engrafted with human immune systems to study CRS, but to date these have not emerged as a standard preclinical screening tool. [22][23][24][25][26][27][28] Here, we describe the development of a humanized mouse model based on the NOD-scid IL2rg null (NSG) mouse to study CRS in vivo. 29,30 We used PBMC engrafted NSG, NSG-SGM3, and NSG-MHC-DKO mice to study cytokine release in response to several immunotherapeutics, including anti-CD3, anti-CD28, Keytruda, anti-thymocyte globulin (ATG), and a TGN1412 analog.…”
Section: Introductionmentioning
confidence: 99%
“…A more reliable T‐cell response to tumors may be expected in systems in which either (1) T‐cell education occurs in a human thymus, such as the BLT HM, or (2) previously educated T cells in human PBMCs are injected into immunodeficient mice. In this environment, mature T cells could be more reasonably expected to recognize and bind to human MHC proteins on an implanted tumor and react appropriately to applied immunotherapies 20,83,84 . However, each of these systems also has critical limitations.…”
Section: Strategies To Improve the Hm Platformmentioning
confidence: 99%
“…They can be systemic or organ-specific and may be different depending on the given immunotherapy, for example anti-CTLA-4 or anti-PD-1/PD-L1 monotherapy or treatment combinations [107]. These irAEs include typically pneumonitis, hepatitis, colitis, nephritis, dermatitis, encephalitis, and adrenal or pituitary insufficiency [108]. Importantly, unexpected irAEs have been observed in skeleton, causing compression, resorptive bone lesions and fractures [109], and inflammatory arthritis after the immunotherapy has been stopped [110].…”
Section: Immunotherapies and Adverse Events In Humanized Mouse Modelsmentioning
confidence: 99%
“…Weaver and colleagues studied nivolumab in a BLT humanized mouse model in NOG and transgenic hGM-CSF and IL-3 NOG (NOG-EXL) mice [108]. Though the humanized BLT-NOG mice had significantly reduced survival compared to humanized BLT-NOG-EXL mice; both strains showed similar adverse effects by nivolumab that are also observed in humans, including pneumonitis, hepatitis, nephritis, dermatitis and adrenalitis.…”
Section: Immunotherapies and Adverse Events In Humanized Mouse Modelsmentioning
confidence: 99%